2020
DOI: 10.3390/vaccines8030386
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Quantification of SARS-CoV-2-Neutralizing Antibodies Using Propagation-Defective Vesicular Stomatitis Virus Pseudotypes

Abstract: Severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2, a new member of the genus Betacoronavirus, is a pandemic virus, which has caused numerous fatalities, particularly in the elderly and persons with underlying morbidities. At present, there are no approved vaccines nor antiviral therapies available. The detection and quantification of SARS-CoV-2-neutralizing antibodies plays a crucial role in the assessment of the immune status of convalescent COVID-19 patients, evaluation of recombinant therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
92
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 29 publications
1
92
0
1
Order By: Relevance
“…Functional assays like virus neutralisation tests are essential to address specific questions related to protective immunity after vaccination or natural infection. However, these type of assays are operated based on in-house protocols and lack standardization across laboratories [16][17][18] . We performed an independent two-centre clinical evaluation of the GenScript cPass™ test, which is based on the principle of an inhibition ELISA, to assess its value for routine diagnostics and as surrogate functional assay to measure neutralising capability in SARS-CoV-2 elicited antibody responses.…”
Section: Discussionmentioning
confidence: 99%
“…Functional assays like virus neutralisation tests are essential to address specific questions related to protective immunity after vaccination or natural infection. However, these type of assays are operated based on in-house protocols and lack standardization across laboratories [16][17][18] . We performed an independent two-centre clinical evaluation of the GenScript cPass™ test, which is based on the principle of an inhibition ELISA, to assess its value for routine diagnostics and as surrogate functional assay to measure neutralising capability in SARS-CoV-2 elicited antibody responses.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the analysis of functional activity of SARS‐CoV2‐reactive T cells showed that the majority of T cells were bi‐ or trifunctional producing Th1 proinflammatory cytokines TNFα, IFNγ, IL‐2, or granzyme B. Because such polyfunctional cells are commonly considered as indicators of protective immunity, 23,24 the detection of polyfunctionality within SARS‐CoV2‐reactive T cells points to their protective antiviral capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry data were analyzed using FlowJo version 10.6.2 (BD Biosciences, San Jose, CA), R version 3.6.2, and Prism version 8 (GraphPad Software, LaJolla, CA). For the virus neutralization assay, a propagation‐incompetent VSV*ΔG(FLuc) pseudovirus system bearing the SARS‐CoV‐2 spike protein in the envelope was incubated with serial dilutions of immune sera prior to infections of Vero E6 cells, as described before 24 . At 18 hours post infection, firefly luciferase (FLuc) reporter activity was determined and the reciprocal antibody dilution causing 50% inhibition of the luciferase reporter calculated (PVN50).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional assays like virus neutralization tests are essential to address specific questions related to protective immunity after vaccination or natural infection. However, these type of assays are operated based on inhouse protocols and lack standardization across laboratories [16][17][18] . We performed an independent two-centre clinical evaluation of the GenScript cPass™ test, which is based on the principle of an inhibition ELISA, to assess its value for routine diagnostics and as surrogate functional assay to measure neutralizing capability in SARS-CoV-2 elicited antibody responses.…”
Section: Discussionmentioning
confidence: 99%